Pola Makan Sehat Siswa Kelas VII SMP Negeri 34 Medan - Nadra Zelina Putri; Arly Mushlih Hayati Br.Lubis; Syakila Mawaddah Caniago; Zubaidah Lubis; Luqman Hafiz; Khairun Nisa; Mawar Nur Ayu; Siti Nurhalijah; Rehulina Br Sembiring; Adzkia Al Adha Nihayatun Nufus; Lisa Septia Dewi Br. Ginting; Ulian Barus; Dalmi Iskandar Sultani (Journal Innovation In Education, 2025)
Nowadays, ready-to-eat food is more popular with teenagers because it is easy and short to serve. Fast food is considered trendy food and is popular among teenagers. Teenagers need to get used to healthy eating patterns to build their bodies. Therefore, research was conducted with the aim of finding out healthy eating patterns for seventh grade students at SMP Negeri 34 Medan. This activity was carried out at SMP Negeri 34 Medan on November 22 2024 in the form of an interview with the theme "Healthy Eating Patterns of Grade VII Students of SMP Negeri 34 Medan ". The research results show that there are still many students who still do not understand the importance of healthy eating patterns, such as adopting breakfast behavior which can help metabolic processes and concentration. After this research was carried out, it could be concluded that this activity produced output, namely increasing insight and increasing students' knowledge about healthy eating patterns.